Analisis Penerapan Perawatan pada Mesin Digester dengan Metode Overall Equipment Effectiveness (OEE) PT. XYZ - Fiqri Arif Anugrah Tanjung; Fadly Ahmad Kurniawan Nasution; Ade Irwan (Universitas Harapan Medan, 2021)
XYZ is a company engaged in the processing of palm oil into crude palm oil (CPO). In processing oil palm fruit, the digester machine is one of the machines that crush the loose fruit so that the pulp of the palm fruit can be separated from the nuts / seeds and this will facilitate the pressing process of the oil palm fruit in a screw press. Total productive maintenance (TPM) is a system that is useful in increasing factory productivity and the efficiency of company production by using machines / equipment effectively used to produce a product. The main purpose of implementing TPM is carried out through the overall equipment effectiveness analysis method to identify and types of damage to critical components that are the object of research and to increase the overall equipment effectiveness value as a performance measure of the results of this study. To determine the comparison of the overall equipment effectiveness value, the calculation of the effectiveness value of the digester machine is carried out using the overall equipment effectiveness method. Based on the results of data processing, it can be concluded that the overall equipment effectiveness value of the digester machine is 3.95%, which is obtained from the availability ratio of 41.24%, the performance efficiency ratio of 157.57 and the rate of quality product of 100%.